Feasibility Study Design And Laboratory Management Of Experimental Animals In Poltekkes Kemenkes Semarang - S.Y Didik Widianto; Sri Hetty Susetyorini; Surati Surati (Jurnal LINK, 2013)
Laboratory is the main supporting to reach the learning aim that appropriate competency for Nutrition Department students. Utilization of experimental animals as objects experiment in the laboratory to test in vivo ( laboratory with experimental animals ) not available yet, this laboratory is important to development of science related with diet, chemical compounds that has a positive role to health. Laboratory of experimental animals is not available yet, therefore necessary to design the laboratory of experimental animals. Purposes of Research : to design laboratory management of experimental animals, management of experimental animals cages and management of experimental animals waste. Design of research includes descriptive qualitative with comparation study in laboratory of experimental animals at Universitas Gajah Mada ( UGM ) and Universitas Negeri Semarang ( UNNES ). Data collection with literature study, interview, visit to laboratory of experimental animals. Results of research : hamster, white mouse and rabbit are used as experiment because of the fisiologis excuses, these animals are able to be simulation model because have some similiars with the condition of human body. Animal source must be from a certified institute that provides experimental animals who is able to guarantee animals health. Original genetic and homogenous. Cage in accordance with necessaries. There are three types : cage enlargement, cage for feeding and mating. Cage must be kept clean. Diet should be made periodically as needed. Management staff who has biology educational background one or two person and two other staff. Laboratory design of experimental animals at Nutrition Department has just been developed as simple applied laboratory, without reproduction management and enlargement of experimental animals. Laboratory management of experimental animals refers to the current system. Design of cage has a size 4m x 4m which is equipped sanitation facilities / sink and prep table. Conclusion : Hamster and white mice are used for experimental animals. The cage treatment and cage maintenance are cage design that is required. One management staff with the biology educational backgroud is required and empowering an existing. Room design 4m x 4m which is equipped a sink and prep table for equipment.